Cadar and Women’s Awrat In Indonesian Qur'an Literature - Indal Abror; M. Nurdin Zuhdi; Iwan Setiawan; Ahmad Suhendra (UIN Sunan Kalijaga Yogyakarta, 2021)
The use of cadar becomes a controversial discussion in Indonesia. However, the majority of scholars consider the cadar is not an obligation in religion. Bearing in mind, there are differences in the limits of women's genitalia or awrat. It shows in the Quranic interpretation of literature in Indonesia that cadar's views lie in the different scholars in interpreting and determining the limits of women's genitalia. This paper uses a comparative method to compare the interpretations of Hasbi Ash-Shiddieqy and Quraish Shihab in understanding verses about the cadar and the limits of women's Awrat (genitalia) in both interpretations. This research method is qualitative and library research. Hasbi Asy-Syiddieqy, in his interpretation of An-Nur, explains that women are obliged to cover their jewelry, while Quraish Shihab considers the cadar is not an obligation in religion because, for him, the face is not part of the awrat (genitalia) that must be covered. The difference can be seen from their educational and scientific backgrounds. Hasbi Asy-Syiddieqy has a background in Islamic law (Fiqh), so the style of interpretation in the book of An-Nur is more nuanced in fiqh. However, Quraish Shihab highlights the nuances of interpretation in the book of Al-Misbah, which tends to imitate the model or style of interpretation of Muhammad Abduh and Rashid Rida. This cadar is part of the need for tahsiniyat (Luxuries). The need for tahsiniyat is a need which if not fulfilled, does not threaten the existence of one of the maqashid ash-shariah (objectives of sharia) and does not cause difficulties.